Unleashing India's innovation : toward sustainable and inclusive growth - Dutz, Mark Andrew (World Bank e-Library., 2007)
India's recent growth rate has been impressive, with real GDP rising by over 8 percent a year since 2004. The country is also becoming a top global innovator for high-tech products and services. Still, India is underperforming relative to its innovation potential. Even a dynamic young population--more than half of whom are under 25 years of age--is constrained when skillstraining and higher education are insufficient. To sustain competitiveness, economic growth, and rising living standards over the long term, India needs to aggressively harness its innovation potential.